Membangun Karakteristik Bangsa Melalui Efektifitas Pendidikan Agama Di Keluarga: (Tinjauan Teoritis dan Praktis Pendidikan Agama Islam Berbasis Studi Interdisipliner) - Siswanto, Heru (MADINAH, 2017)
Man is naturally born in the world in a state of weakness. Both physically and psychically weak. But in such circumstances he has an innate potential. This innate potential requires development through guidance and maintenance, especially at the level of early childhood. Intellect and other mental functions will only function if maturity and maintenance and guidance can be directed to the exploration of its development. Just as physical or physical man will only function perfectly if maintained and trained continuously. That ability can not be met simultaneously but through the stages. Likewise, the development of religion in children. This shapes the child’s personality at a later stage.